Magnetic resonance force microscopy and a single-spin measurement - Berman, Gennady P., 1946- (World Scientific, 2006)
With contributions by internationally re-knowned authorities and experts in the field of ultrasonic imaging, this book provides comprehensive reviews on basic physical principles and applications of emerging and rapidly developing therapeutic techniques. In specific, reviews of mechanisms for bioeffects of ultrasound relevant to therapeutic applications, high intensity focused ultrasound and its application in surgery, ultrasound assisted target drug and gene delivery, as well as transdermal drug delivery are discussed. The book will be a useful reference source for graduate students, academics and researchers.